FOCUS: A full-orbit CUDA solver for particle simulations in magnetized plasmas - Clauser, Cesar Fernando (2018)
A Full-Orbit CUDA Solver for particle simulations in plasmas, FOCUS, has been developed. The code follows exact particle trajectories by solving Newton’s equations with the Lorentz force. The code can use fields calculated analytically or numerically and it is also possible to use the information provided by equilibrium reconstruction and transport codes. FOCUS has an elastic collisions module which covers the whole particle energy range in magnetic fusion devices. Moreover, an atomic collision module was also included to simulate the interaction of the test particles with neutral or partially ionized species. Regarding performance, the main feature is that the code runs on GPUs, allowing the simulation of a large number of particles using moderate computational resources. Different versions of the code have been used in several papers. Here we present a complete description of its capabilities, the basis physics included and detailed information about the numerical algorithms employed. Finally, some examples are presented.